Eugenia (Myrtaceae) from Mexico: checklist, distribution, and conservation assessments - Gala, Victor C. Uc; Valdemarin, Karinne Sampaio; Lucas, Eve; Negrão, Raquel; Mazine, Fiorella F. (Phytotaxa, 2023)
Myrtaceae is represented in Mexico by 10 genera and ca. 109 species mainly occurring in warmer climatic zones. Eugenia is one of the most diverse genera in Myrtaceae, with about 1,150 species, distributed from Mexico, Cuba and the Antilles to Uruguay and Argentina, with fewer representatives in Africa and Southeast Asia. This study presents a checklist of the 87 species of Eugenia that occur in Mexico as well as provides assessments of environmental threat for each species. The checklist was prepared in stages, gathering data from international databases, consulting relevant bibliography (mainly Mexican Floras), personal visits to key herbarium collections (MEXU, CICY and K), and analysis of specimen images available online. Extinction risk assessments follow the categories and criteria of the IUCN Red List of Threatened species version 3.1. calculating the extent of occurrence (EOO) and area of occupancy (AOO) parameters using the GeoCat software (Geospatial Conservation Assessment Tool). Extinction risks are provided for eighty-seven species of Eugenia, including notes on species distributions. Mexican states with the highest number of species of the genus are Chiapas and Veracruz, with 48 and 31 species, respectively. Forty-six species are endemic to Mexico, which represents 53% of the total of species occurring in the country. Regarding extinction risk, from a total of 87 species, 33 species (38%) are assessed with a threatened category, with 7 Critically Endangered (CR), 14 Endangered (EN), and 12 Vulnerable (VU); 54 species are not threatened, 42 of these rated as Least Concern (LC) and 12 as Near Threatened (NT). This study reveals the degree of extinction risk that exists to native or endemic Mexican Eugenia species, and highlights the urgent need to take action to protect, conserve and monitor their populations in the wild.